Hasidism and politics : the kingdom of Poland, 1815--1864 - Wodziński, Marcin (The Littman Library of Jewish Civilization, 2013)
The book analyses the development of political relations between the Kingdom of Poland and the hasidic movement, and demonstrates the distinctively modern character of hasidic political activity.